POLA KOMUNIKASI MASYARAKAT MELAYU DAN JAWA DI KECAMATAN SEI SUKA KABUPATEN BATUBARA - Sulaiman Ahmad (ADISAM PUBLISHER, 2023)
There are two tribes in Kecamatan Sei Suka Kabupaten Batubara, namely the Melayu tribe and the Javanese tribe. The purpose of this research is to study how people from different cultural backgrounds communicate in the village of Sei Suka. This research is a qualitative descriptive field research with the aim of accurately establishing systematic qualitative descriptive facts and the characteristics of certain regional groups. This research data collection methods include interviews, observation, and documentation. The result of the research is that from the results of this study it was found that people who used to use oral communication from the local language, the language was interpreted and used in a group environment and was considered a common language. While the nonverbal communication used in the communication activities of the Melayu and Javanese people in Kecamatan Sei Suka Kabupaten Batubara are body language, appearance and clothing. Nonverbal language is used to support the meaning of information in society using nonverbal language to strengthen and complement language so that it can communicate effectively. Supporting factors in this intercultural communication process are the ability to communicate, mutual trust, friendly and polite attitude, interest in communicating, and adaptability